Triple Divorce in a Single Utterance in Libyan Dar al-Ifta Fatwas: The Maqāṣid Distribution on Institutional Duality - Masuwd, Mowafg; Ayad, Nahid; Alrumayh, Safa; Abdulghani, Naser (MUI Sulawesi Selatan, 2026)
This study examines how the Libyan Dar al-Ifta (2012-2016) implements ahkam on triple divorce pronounced in a single utterance (ṭalāq al-thalāth bi-lafẓ wāḥid) or closely related patterns which related to divorce counting. Using a qualitative, document-based design method and juristic content analysis, the study examines a purposive corpus of published fatwas addressing (1) explicit numerical pronouncements “by three”, (2) repeated utterances (ṭāliq / hiya ṭāliq) framed as emphasis versus multiple enactments, and (3) conditional divorce and divorce oaths. Results show that the majority juristic position and authoritative transmissions are used to enforce the fatwa (explicit-number and conditional “three”). Repetition treated as emphasis under constrained intention. Moreover, the study reveals an institutional duality in Libya in which fatwas often enforce conditional or oath-based triggers and count explicit-number pronouncements as three if the awareness is present. On the other hand, Law No. 10 of 1984 limits the effect of numbered divorce to one, prevents conditional divorce and divorce-oath effects. This contradiction between the fatwas and the law is interpreted as a distribution of Maqāṣid across institutions, where prevention and safeguarding the seriousness of divorce language are emphasized in fatwa practice, while harm reduction and family stability are institutionalized through legal policy and procedure. This study, empirically, contributes the ongoing discussions of fatwa reasoning in society and clarifies how the tension between Ibn Abbas hadith and the majority pathway is managed and understood as evidence or an exception rather than a rule.